1982
DOI: 10.1073/pnas.79.18.5631
|View full text |Cite
|
Sign up to set email alerts
|

Restriction map variation in the Adh region of Drosophila.

Abstract: Restriction maps of a 12,000-nucleotide region containing the alcohol dehydrogenase (Adh) locus of the second chromosome of Drosophila were determined for (i) 18 independent second chromosome stocks of D. melanogaster established from several natural populations and (ii) five closely related Drosophila species. All of the detected map differences appear to lie outside the Adh coding block. Four polymorphic restriction sites and four insertion/deletion variants were identified among D. melanogaster chromosomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
57
3

Year Published

1983
1983
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 34 publications
8
57
3
Order By: Relevance
“…The imbalance between these two mutagenic events can be a driving force that decreases the genome size and also the intron size. We observed gaps (insertions and deletions) of fairly small sizes in non-coding sequences, the longest one being a 16 nt deletion, which is consistent with the previous observations of short deletions [20][21][22]. The dis- tribution of gap lengths found in the alignment of human/ rodent introns also indicates a higher frequency of smaller gaps (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…The imbalance between these two mutagenic events can be a driving force that decreases the genome size and also the intron size. We observed gaps (insertions and deletions) of fairly small sizes in non-coding sequences, the longest one being a 16 nt deletion, which is consistent with the previous observations of short deletions [20][21][22]. The dis- tribution of gap lengths found in the alignment of human/ rodent introns also indicates a higher frequency of smaller gaps (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…This theoretical prediction suggests that the selective benefit of a host allele increases with the number of TE copies whose transposition it can suppress. Given the TE transposition rate [10 25 10 24 (Nuzhdin and Mackay 1995;Nuzhdin et al 1997;Maside et al 2000Maside et al , 2001 For example, a host allele that can reduce half of the transposition rate of a subset of TE families with a total of 1000 copies can have a selection coefficient as large as 10 25 , which would be strong enough to overcome the effect of genetic drift in D. melanogaster [N e 10 6 (Langley et al 1982;Kreitman 1983)]. Accordingly, unlike the arms race between host and horizontally transferred pathogens, where strong selective benefit comes from the precise targeting of the host allele to a specific pathogen variant, the antagonistic interaction between TEs and host variants that can target the aggregated influence of multiple vertically inherited TE families could be the main force driving the fast evolution of host TE-interacting genes…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygosity per nucleotide has been estimated to be 0.001, with 0.5% of the nucleotide sites polymorphic (8) (8,9) but in Drosophila the two appeared to be similar (7,12 (25) reported a strain difference in the size of the spacer region at the 87A7 hsp70 locus. This difference corresponds to insertion B in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1 (unpublished data). In a detailed study of the hsp70 genes from 87A7 and 87C1 using DNA sequence analysis, Mason (53,54), although Tn5 appears to insert at random (55 (12), this suggests that selection can detect the effects of DNA insertion at some distance from coding elements and prevent such variants from becoming fixed in the species. In the f3-globin gene cluster of higher primates it has recently been suggested that even the rate of nucleotide substitution may be lower outside the coding regions than that for silent substitutions within them (57).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation